Upaya Peningkatan Hasil Belajar Mahasiswa Program Studi Diploma III Fisioterapi Melalui Model Skenario Belajar Berdasar Masalah Terintegrasi pada Mata Kuliah Fisioterapi untuk Kasus Susunan Syaraf Tepi (Lembaga Penerbitan Universitas Esa Unggul, 2005)
The aims of this research were (1) to obtain the developmental of the scenario intergrated problem based learning model and (2) to know can the use of scenario intergrated problem based learning increase the student’s achievement. The subject of this research was all forth semestres of student of Physio Therapy department in Muhammadiyah University of Surakarta. The research conducted as long as one semester with the result was the developmental model of the Scenario intergrated problem based learning. In the and of the study, researcher obtained two results. One was that the developmental model of scenario intergrated problem based learning consits of (9) nine steps, namely (1) give a scenario, (2) clarify terms and concepts, (3) define the problem, (4) Analysis the problem with brainstroming, (5) Summarize and make a map, (6) formulate the learning objective and define the individual / self study with read a jornal, consult an expertise, etc, (7) Prepare a presentation, (8) Synthesize and do a test toward a new information, (9) Elaboration. Second, The achievement of subject of this study can be increased by the use of this method.Keywords: Scenario, Intergrated Problem, Based Learning